"I Had a Little Bit of a Bloke Meltdown…But the Next Day, I Was Up": Understanding Cancer Experiences Among Aboriginal Men. Issue 3 (May 2017) - Newman, Christy E.; Gray, Rebecca; Brener, Loren; Jackson, L. Clair; Dillon, Anthony; Saunders, Veronica; Johnson, Priscilla; Treloar, Carla
Abstract : Background: Although cancer in indigenous populations is receiving increased research attention, there is a gap in understanding the particular experiences of Aboriginal men. Objective: The aim of this study is to integrate a range of primary and secondary accounts of the experiences of Aboriginal men in engaging with a cancer diagnosis and treatment in Australia. Methods: Secondary analysis of qualitative interviews (n = 54) conducted between 2008 and 2011 revealed recurrent themes regarding the cancer experiences of Aboriginal men in a subset of participant interviews (n = 23). The analysis reports themes that spanned the accounts of Aboriginal men with cancer (n = 6) and those of their carers (n = 12) and clinicians (n = 5). Results: Recurrent beliefs about the cancer experiences of Aboriginal men included that they "avoid seeking help" for health matters, including cancer symptoms, and to "get on with it, " "not talk about it, " and "manage without fuss" after a cancer diagnosis. Although some men described having to "accept vulnerability, " emphasis was placed on appreciating men's desire to "protect cultural roles" and "connect with family and culture" throughout care and treatment, including through humor. Conclusions: Men's accounts of the experiences of cancer diagnosis and care reveal more than simply individual challenge, extending to encompass the very real social and economic implications of illness and vulnerability for Aboriginal men today. Implications for Practice: Aboriginal men could be better engaged with cancer diagnosis and treatment if greater attention was paid to recognizing preferred approaches, including pragmatism and humor, and supporting connections to family and culture throughout the cancer journey.